Invocação para o fim: o sertão como arquivo - Natália de Sousa Moura (2020)
Questioning the ways of knowing, mapping, and archiving instituted by modern thought, this thesis seeks to articulate disorientation as a possibility of coping and escaping modern ways of knowing based on Denise Ferreira da Silva’s and Diana Taylor’s thought. The production and transmission of knowledge that defines the world as we know it derives from the written archive, as well as its inscription in history, and is mediated by Cartesian, linear, binary, and arbitrary guidance systems, which dictate what remains outside and what is allowed inside, for what or who the past, present and future are destined to. This construction of thought occurs from the institution and fictionalization of a model to be followed that has its consolidation in the invasion and colonization of the territories known today as America (s) by the Europeans and in the expropriation of bodies through slavery, with the creation of the racial and cultural Other as opposed to a universal Self. I write from the deep understanding that decolonization is not a metaphor (TUCK, YANG, 2012) or, in other words, it is not a new way of naming justice, but something articulated with the destruction of the idea of the world that we have known (FERREIRA DA SILVA, 2019; MOMBAÇA, 2019). And in doing so, I connect this writing to a practice of radical research and imagination imbued by places (and bodies) marked as “ends of the world” (fins de mundo), wild, backward, demonic, dusty, infernal in the sense that they are survivors of the ends. Suddenly I can glimpse the fictionalization of other possible worlds outside modern logic. The primary fictional terrain of the thesis is Lisieux, a district in Ceará northwestern hinterland, located in Brazil northeast, an “end of the world” (fim de mundo). In its official history, the Church village stands as a landmark of origin (60 years), following an idea of linear time and progress established since colonization. Therefore, the archive that tells the village story stays frozen in an arbitrary sequence, and its limits are imposed by imaginary lines that serve the logic determined by those with power, that is, the Church and landowners. Nonetheless, this place location as and in the hinterland ensures that there is always something that escapes, that blurs the view, that cannot be entirely ascertained. The very floor where we walk on tells of a much longer time structure than that of our body can understand. Its archive is alive, articulating itself more as an apparition, performance (incorporation), and imagination than as “archivable” and capturable truth, document, and institution. It is a radical, impermanent, disorienting, threatening, premonitory, and infinite file.